A Content Analysis of Empirical Parent Engagement Literature. Issue 1 (2nd January 2022) - Wymer, Brooke; Swartz, Melissa R.; Boyd, Liz; Zankman, Melissa; Swisher, Sierra
ABSTRACT: Early intervention in child mental health is crucial due to the potential for adverse life outcomes when not treated early in development. Parent engagement primarily determines whether a child will attend mental health services until successful completion. Our content analysis explored empirical research studies of parent engagement interventions in child mental health services to address gaps in the current literature. We synthesized the trends and common themes across parent engagement practices to provide implications for the counseling field and recommend future research.